2019
DOI: 10.3390/ma12172806
|View full text |Cite
|
Sign up to set email alerts
|

Sound Insulation and Reflection Properties of Sonic Crystal Barrier Based on Micro-Perforated Cylinders

Abstract: A sonic crystal barrier, consisting of empty micro-perforated cylindrical shells, was built on the campus at the Universitat Politècnica de València in 2011 and characterised by using a non-standardised measurement technique. In this paper, the sonic crystal barrier, upgraded with rubber crumb inside the micro-perforated cylindrical shells, was characterised by using standardised measurement techniques according to EN 1793-5 and EN 1793-6. As a result of the characterisation, sound insulation properties of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Authors [1,25,26,[54][55][56][57][58] have shown that the foreground and background sounds affect the perception of the environment differently. It is the background noise that correlates with space perception.…”
Section: Discussionmentioning
confidence: 99%
“…Authors [1,25,26,[54][55][56][57][58] have shown that the foreground and background sounds affect the perception of the environment differently. It is the background noise that correlates with space perception.…”
Section: Discussionmentioning
confidence: 99%
“…So, the first decision is considering the lowest frequency in the traffic noise spectrum of international standard EN 1793-3 [8], 100 Hz. At this frequency the SNCB is almost transparent, having an insignificant insulation of only 2 or 3 dB [9]. The noise source will be a car moving at 108 Km/h in a highway section of 6 meters.…”
Section: Anc System For Scnb With Ddqn Architecturementioning
confidence: 99%
“…Participatory tools such as focus groups, questionnaires, and sound walks facilitate this engagement [8,9]. After gathering the environmental condition evolution and the evolving area's public opinion, several noise-reducing measures can be exploited to solve targeted environmental acoustic problems, like low-noise road pavements, noise barriers, regulatory car speed reduction, and viability modification [3,[10][11][12][13][14][15]. Moreover, targeted solutions (like sound-proofing windows or louvres) can be developed for buildings where acoustic comfort is critical for indoor activities, such as schools, hospitals, or offices [16].…”
Section: Introductionmentioning
confidence: 99%